USE OF A JUST IN TIME TEACHING / FLIPPED CLASSROOM QUESTIONNAIRE FOR THE DETECTION OF IMPROVEMENTS IN UNIVERSITY EDUCATIONAL MATERIALS - Vas, Juan Ángel Contreras; Andrade, Malena G. Melo; Masa, Juan Arias; Vasco, y Juan Ramón Moya (IJRDO- Journal of Educational Research, 2017)
With this experimental research, we try to detect the possibility of improving the educational materials used in university teaching. The creation and improvement of educational materials go through several stages such as: defining contents to be taught, selecting sources of information, process materials, make the information available to the students, be studied by them, check the assimilation, to detect defects of assimilation, improvement of materials and, to verify that the improvement made generates the appropriate effects on students. This article demonstrates the realization of an experiment of detection, improvement and verification of that improvement of some university educational materials. To carry out the task, we use questionnaires like Just in Time Teaching / Flipped Classroom to obtain information from the students, and the use of mixed methodologies for the detection of materials to improvement and verification of the effects that has had the improvement in the application of the same.